The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/genes14040806
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Gene Editing System Can Alter Gene Expression and Induce DNA Damage Accumulation

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) and the associated protein (Cas) gene editing can induce P53 activation, large genome fragment deletions, and chromosomal structural variations. Here, gene expression was detected in host cells using transcriptome sequencing following CRISPR/Cas9 gene editing. We found that the gene editing reshaped the gene expression, and the number of differentially expressed genes was correlated with the gene editing efficiency. Moreover, we found that alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Editing of NFYA gene resulted in 32% decrease of mRNA and 66.6% decrease of protein. Previous finding found that changes in the mRNA levels after gene editing are positively correlated with the gene editing efficiency [14]. Several manipulations of mRNA after CRISPR/Cas9 were documented.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Editing of NFYA gene resulted in 32% decrease of mRNA and 66.6% decrease of protein. Previous finding found that changes in the mRNA levels after gene editing are positively correlated with the gene editing efficiency [14]. Several manipulations of mRNA after CRISPR/Cas9 were documented.…”
Section: Discussionmentioning
confidence: 93%
“…Ten exons (1-5 and 16-20) produce the standard form of CD44 (CD44s; ~85 kDa) and known as "constant" exons. The ten central exons (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) subjected to extensive alternative splicing to form splicing variants (CD44v isoforms) (CD44v) and known as variant exons 1-10 (v1-10) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…73 The above could be explained because during the active period of gene editing, changes occur in chromosome segregation and nuclear division, evidencing a probable mechanism for the induction of chromosomal alterations following gene editing. 88 Overall, the research carried out to date shows a limitation for the application of DSB-inducing CRISPR therapy in the clinic, so it is important to consider the possibility that extensive chromosomal rearrangements may be induced as a result of the application of this gene editing technology.…”
Section: Crispr-cas9 Limitations-induction Of Chromosomal Alterationsmentioning
confidence: 99%